La confiance : approches économiques et sociologiques - Gagnon, Mona-Josée (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, "La confiance : approches économiques et sociologiques," edited by Christian Thuderoz, Vincent Mangematin and Denis Harrisson.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Trust (Psychology)